L2 Learners’ Sensitivity to the Transitivity Bias Continuum in English Verbs - Ji Hyon Kim (언어학, 2020)
The present study examines whether Korean L2 learners of English are sensitive to the continuum of transitivity bias in English verbs. In an acceptability judgment task, thirty-six English verbs differing in degrees of transitivity bias ranging from obligatorily intransitive to high-transitive verbs were used in both transitive and intransitive sentence frames. Results showed that the transitivity preference index, which was calculated as the difference in mean acceptability ratings between the transitive and intransitive uses of each verb, showed a significant positive correlation with the verbs’transitivity quotients. These results support and extend previous studies by showing that L2 learners are not only able to distinguish categorical classes of verbs, but are also sensitive to gradable differences in verb transitivity bias. KCI Citation Count: 0